Electroacupuncture-induced activation of GABAergic system alleviates airway inflammation in asthma model by suppressing TLR4/MyD88/NF-κB signaling pathway - Ruisong Gong; Xiaowen Liu; Jing Zhao; Jing Ni (Chinese Medical Journal, 2023)
Abstract. Background:. Electroacupuncture (EA) has been shown to attenuate airway inflammation in asthmatic mice; however, the underlying mechanism is not fully understood. Studies have shown that EA can significantly increase the inhibitory neurotransmitter γ-aminobutyric acid (GABA) content in mice, and can also increase the expression level of GABA type A receptor (GABAAR). Furthermore, activating GABAAR may relieve inflammation in asthma by suppressing toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear factor-kappa B (NF-κB) signaling pathway. Therefore, this study aimed to investigate the role of GABAergic system and TLR4/MyD88/NF-κB signaling pathway in asthmatic mice treated with EA. Methods:. A mouse model of asthma was established, and a series of methods including Western blot and histological staining assessment were employed to detect the level of GABA, and expressions of GABAAR and TLR4/MyD88/NF-κB in lung tissue. In addition, GABAAR antagonist was used to further validate the role and mechanism of GABAergic system in mediating the therapeutic effect of EA in asthma. Results:. The mouse model of asthma was established successfully, and EA was verified to alleviate airway inflammation in asthmatic mice. The release of GABA and the expression of GABAAR were significantly increased in asthmatic mice treated with EA compared with untreated asthmatic mice (P < 0.01), and the TLR4/MyD88/NF-κB signaling pathway was down-regulated. Moreover, inhibition of GABAAR attenuated the beneficial effects of EA in asthma, including the regulation of airway resistance and inflammation, as well as the inhibitory effects on TLR4/MyD88/NF-κB signaling pathway. Conclusion:. Our findings suggest that GABAergic system may be involved in mediating the therapeutic effect of EA in asthma, possibly by suppressing the TLR4/MyD88/NF-κB signaling pathway.